From the Editors - Esterhuyse, Abel; Liebenberg, Ian (Scientia Militaria - South African Journal of Military Studies, 2013)
The military profession, like the scholarly one, faces the dualistic conundrum of learning from the past in an effort to shape future reality. The question is not only how to balance the study of history with concerns of, in many cases, the unpredictable, foreseeable future. It is also a matter of how to study both history (in an effort to draw the right lessons from past experience) and contemporary trends (to temper our expectations of the future). Historically, informed guesswork governed by what Colin Gray refers to as the ‘golden rule of prudence’ is the best way to ‘gamble’ with the future and ensure that plans are not only governed by hope.1 As editors of a journal on military studies our challenge is always to find a careful balance in the content between looking at what has happened and what is due to influence future strategic and tactical realities.